Clopidogrel in cardiovascular disease treatment: modern clinical recommendations - I. S. Yavelov (Кардиоваскулярная терапия и профилактика)
The article is devoted to antiaggregant clopidogrel place in cardiovascular disease treatment. It contains modern views and recommendations by carious experts from most reputable international medical organizations